2017
DOI: 10.21276/apalm.1427
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Histopathological Study of Breast Lesions with cytology and mammography as a measure of internal quality and diagnostic accuracy

Abstract: Background: Breast cancer is the one of the leading causes death in women. Triple test approach has been widely accepted in asymptomatic women for the preoperative diagnosis of the breast lesions. Triple test includes clinical examination, mammography and Fine Needle Aspiration Cytology (FNAC) to differentiate between neoplastic and non-neoplastic lesions, histopathological confirmation being the gold standard for neoplasticlesions and best management plan for the patient.The aim was to study the histopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The association was much clear in false positives involving a cytology examination or biopsy, and in women with a family history of breast cancer. [14] Mulka A et al (2017) concluded that Mammography can diagnose more malignant lesions than benign because mammography was done after 35 years of age. It showed that majority of non-neoplastic cases are reported in the third decade.…”
Section: Resultsmentioning
confidence: 99%
“…The association was much clear in false positives involving a cytology examination or biopsy, and in women with a family history of breast cancer. [14] Mulka A et al (2017) concluded that Mammography can diagnose more malignant lesions than benign because mammography was done after 35 years of age. It showed that majority of non-neoplastic cases are reported in the third decade.…”
Section: Resultsmentioning
confidence: 99%
“…Breast malignancies are most often encountered and the second most common malignancy in Indian women. The incidence rate of breast malignancies in India is around 85 per 10,000 women per year [3,4] . Benign breast diseases because of their high incidence and cancerous potential of some of the histological subtypes deserve attention [5] .…”
Section: Introductionmentioning
confidence: 99%